2019
DOI: 10.1155/2019/7395769
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the Highest Plantar Pressure Regions in Patients with Diabetes and Its Association with Peripheral Neuropathy, Gender, Age, and BMI: One Centre Study

Abstract: The abnormal plantar pressure distribution and value play a key role in the formation of plantar calluses and diabetic foot ulcer. The prevalence of the highest pressure different distribution and its association with various factors among patients with diabetes is not well known. The study purpose was to evaluate the prevalence of different regions for the highest pressure on the sole and its association with selected factors among patients with diabetes. Medical records of nonulcer patients were retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 68 publications
1
29
0
4
Order By: Relevance
“…Considering that the foot is the most inferior part of the body, it serves as a base of support as well as propulsion for movement during activities of daily living. [ 1 , 2 ] Indeed, there is a general agreement that proper biomechanics of the foot is responsible for preserving the symmetrical distribution of plantar pressure, and consequently to maintain proper body posture. [ 1 ] Furthermore, several researchers have reported that pressure distribution in the human foot varies considerably by participant's posture and health condition of the foot.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that the foot is the most inferior part of the body, it serves as a base of support as well as propulsion for movement during activities of daily living. [ 1 , 2 ] Indeed, there is a general agreement that proper biomechanics of the foot is responsible for preserving the symmetrical distribution of plantar pressure, and consequently to maintain proper body posture. [ 1 ] Furthermore, several researchers have reported that pressure distribution in the human foot varies considerably by participant's posture and health condition of the foot.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity has become a major global epidemic affecting more than 300 million people, and it is the most important risk factor leading to the onset of T2D [36,37]. BMI has been used as a surrogate marker of obesity and as one of the predictor variables in most diabetes risk models [38][39][40][41]. However, BMI does not reflect central obesity.…”
Section: Discussionmentioning
confidence: 99%
“…The structure of bones, muscles and joints facilitates stability by sustaining and supporting vigorous strain or pressure during standing and walking. The physiological pattern of distribution of pressure on the sole is almost symmetrical and gives the foot, and hence our body, an optimum exibility [21]. Most people comprise a signi cant part of their lives in a standing position.…”
Section: Discussionmentioning
confidence: 99%